Macroprudential and monetary policies: implications for financial stability and welfare - Rubio, Margarita; Carrasco-Gallego, José A. (Elsevier, 2014)
In this paper, we analyze the implications of macroprudential and monetary policies for business cycles, welfare, and financial stability. We consider a dynamic stochastic general equilibrium (DSGE) model with housing and collateral constraints. A macroprudential rule for the loan-to-value ratio (LTV), which responds to credit growth, interacts with a traditional Taylor rule for monetary policy. We compute the optimal parameters of these rules both when monetary and macroprudential policies act in a coordinated and in a non-coordinated way. We find that both policies acting together unambiguously improves the stability of the system. In both cases, this interaction is welfare improving for the society, especially in the case of the non-coordinated game. There is though a trade-off between borrowers and savers. However, borrowers can compensate the saver’s welfare loss View the MathML sourcela Kaldor–Hicks to achieve a Pareto-superior outcome.